Implementing Competence-Based Advanced Level Human Geography Framework at One High School in Zimbabwe During The Covid 19 Era - Shonhiwa Tawanda; Chikuvadze Pinias (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2023)
This paper sought to gain insight into the implementation of the new Competence-Based Advanced Level Human Geography framework during COVID-19 era. The methodological lens comprised of the interpretivist paradigm and qualitative approach guided the data sourcing and analysis. The sample was made up of thirty Advanced Level Geography students and six teachers selected through snowballing. Data sourced through the literature method and personal interview were analyzed according to emerging themes. Findings acknowledged the existence of policies enabled the creation of safe learning environments during the COVID-19 era. The implementation of the new framework during the COVID-19 era was grounded in student-centred approach augmented by e-learning platforms. However, during this era some challenges were encountered in the implementation of the new framework. In conclusion through the implementation of the new framework during the COVID-19 era learning activities shifted from the traditional face-to-face to online student-centered interactions. It’s recommended that through partnerships schools can invest heavily in ICTs for smooth operations amidst disasters